Morroniside ameliorates inflammatory skeletal muscle atrophy via inhibiting canonical and non-canonical NF-κB and regulating protein synthesis/degradation - Yi, Xiangjiao; Tao, Jianguo; Qian, Yu; Feng, Feng; Hu, Xueqin; Xu, Taotao; Jin, Hongting; Ruan, Hongfeng; Zheng, Hou-Feng; Tong, Peijian (Frontiers in Pharmacology, 2022)
No drug options exist for skeletal muscle atrophy in clinical, which poses a huge socio-economic burden, making development on drug interventions a general wellbeing need. Patients with a variety of pathologic conditions associated with skeletal muscle atrophy have systemically elevated inflammatory factors. Morroniside, derived from medicinal herb Cornus officinalis, possesses an anti-inflammatory effect. However, whether and how morroniside combat muscle atrophy remain unknown. Here, we identified crucial genetic associations between TNFα/NF-κB pathway and grip strength based on population using 377,807 European participants from the UK Biobank dataset. Denervation increased TNFα in atrophying skeletal muscles, which inhibited myotube formation in vitro. Notably, morroniside treatment rescued TNFα-induced myotube atrophy in vitro and impeded skeletal muscle atrophy in vivo, resulting in increased body/muscles weights, No. of satellite cells, size of type IIA, IIX and IIB myofibers, and percentage of type IIA myofibers in denervated mice. Mechanistically, in vitro and/or in vivo studies demonstrated that morroniside could not only inhibit canonical and noncanonical NF-κB, inflammatory mediators (IL6, IL-1b, CRP, NIRP3, PTGS2, TNFα), but also down-regulate protein degradation signals (Follistatin, Myostatin, ALK4/5/7, Smad7/3), ubiquitin-proteasome molecules (FoxO3, Atrogin-1, MuRF1), autophagy-lysosomal molecules (Bnip3, LC3A and LC3B), while promote protein synthesis signals (IGF-1/IGF-1R/IRS-1/PI3K/Akt and BMP14/BMPR2/ALK2/3/Smad5/9). Moreover, morroniside had no obvious liver and kidney toxicity. This human genetic, cells and mice pathological evidence indicates that morroniside is an efficacious and safe inflammatory muscle atrophy treatment and suggests its translational potential on muscle wasting.